A comparative analysis of population growth in China and Egypt : people, policies and prospects : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts (Politics) in the School of People, Environment and Planning at Massey University, Albany campus, New Zealand - Yu, Yang; Yu, Yang (Massey University, 2011)
Despite their geographical locations and historical disassociations, China and Egypt face one essential identical issue in common--the problem of over population. This study compares population growth in China and Egypt in terms of people, policies and prospects for economic development. It argues that China and Egypt faced a population crisis that was undermining economic development since the 19th century and this issue of excessive population growth continues to be on the top of the political agenda in the 21st century. Furthermore China and Egypt both have experienced three stages of population development in terms of family planning policies. For China, the first phase of family planning programs began in the 1950s and this was followed by further waves of development in the 1960s and the one child policy in the 1970s. For Egypt, the first phase of Cairo’s family planning program began in 1965 and this was also accompanied by two more stages of development, one in the 1970s and the other in the 1980s. The results of these family planning programs were impressive. China and Egypt both experienced extraordinary fertility decline since the 1980s. Despite these achievements in family planning however, China and Egypt is expected to experience further waves of population increase in the foreseeable future. This would no doubt continue to challenge these countries’ prospect for economic development.
Keywords: Overpopulation; Population growth; Family planning